2015
DOI: 10.1016/j.geoderma.2014.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Potential of integrated field spectroscopy and spatial analysis for enhanced assessment of soil contamination: A prospective review

Abstract: a b s t r a c tThere are tens of millions of contaminated soil sites in the world, and with an increasing population and associated risk there is a growing pressure to remediate them. A barrier to remediation is the lack of cost-effective approaches to assessment. Soil contaminants include a wide range of natural and synthetic metallic and organic compounds and minerals thus making analytical costs potentially very large. Further, soil contaminants show a large degree of spatial variation which increases the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
173
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(178 citation statements)
references
References 214 publications
1
173
0
4
Order By: Relevance
“…As stated by Horta et al (2015), remediation rates on identified contaminated sites are quite modest:…”
Section: Review Of Contaminated Sitesmentioning
confidence: 98%
See 1 more Smart Citation
“…As stated by Horta et al (2015), remediation rates on identified contaminated sites are quite modest:…”
Section: Review Of Contaminated Sitesmentioning
confidence: 98%
“…Panagos et al (2013) estimated contaminated sites and potentially contaminated to be around 0.005 sites per capita for the European Union and a population of 1 billion. Based on these figures, Horta et al (2015) estimated emerging economies to have 0.0025 contaminated sites and potentially contaminated per capita, their population being 2 billion, developing economies to have 0.001 contaminated sites and potentially contaminated per capita, their population being 4 billion. At global level, the estimates of contaminated sites and potentially contaminated are then between 10 million and 20 million sites (including uncertainties).…”
Section: Review Of Contaminated Sitesmentioning
confidence: 99%
“…In addition, the electromagnetic radiation spectrum in the near-infrared region contains useful information about environmental sample constituents such as soil that can be used for prediction of metal concentrations [25,28,33]. For instance, the absorption features associated with electronic transitions of Fe 3+ and Fe 2+ ions in Fe-bearing minerals can be found in the near-infrared region at 780-1200 nm [33][34][35]. In addition, the absorption features of metals associated with molecular vibrations of organic and inorganic functional groups in organic matter, silicates, carbonates, and water can be found in near infrared at 780-2500 nm region [24,33,34,36].…”
Section: Application Of Near-infrared Spectroscopy (Nirs) For Analysimentioning
confidence: 99%
“…For instance, the absorption features associated with electronic transitions of Fe 3+ and Fe 2+ ions in Fe-bearing minerals can be found in the near-infrared region at 780-1200 nm [33][34][35]. In addition, the absorption features of metals associated with molecular vibrations of organic and inorganic functional groups in organic matter, silicates, carbonates, and water can be found in near infrared at 780-2500 nm region [24,33,34,36].…”
Section: Application Of Near-infrared Spectroscopy (Nirs) For Analysimentioning
confidence: 99%
See 1 more Smart Citation